Tourism Development in Langsa, Indonesia: An Overview of Tourist Attractions and Accommodation - Nurlina, Nurlina (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This study provides an overview of the development of tourism destinations, precisely tourist attractions and accommodation in Langsa, Indonesia. Data collection in this research through secondary data collection at related institutions and data analysis descriptively qualitative. The results of this study indicate that there are six main tourist objects. The number of tourist visits by attractions from month-over-month during the year 2016, increasing. The most visited attractions are the city forest park, mangrove forests, culinary centers, Vitra Tirta Raya Swimming Pool, and Mutiara Water Park. The increase in the number of visits this tour, especially on tourist objects managed by government companies caused by the better management of tourism and its supporting facilities. The Municipal Government of Langsa has sought to develop tourism with all its facilities to address several development challenges, including poverty reduction, local economic development, and sustainability.